2023
DOI: 10.1177/10249079231175434
|View full text |Cite
|
Sign up to set email alerts
|

External validation of the Oakland score to assess safe hospital discharge among adult patients with acute lower gastrointestinal bleeding in an accident and emergency department in Hong Kong

Abstract: Objective: To externally validate the use of the Oakland score in identification of low-risk lower gastrointestinal bleeding patients who can be safely managed without hospitalisation in an accident and emergency department in Hong Kong. Methods: This single-centre retrospective cohort study included adult patients who attended the accident and emergency department for lower gastrointestinal bleeding and were subsequently admitted to hospital from 1 January 2020 to 31 December 2020. Safe discharge was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…However, there were more adverse events [9]. Furthermore, the Fong study found that a threshold of ≤11 points resulted in a sensitivity of safe discharge at 97% [10]. Similar results were also seen in the 2021 Martin et al study.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…However, there were more adverse events [9]. Furthermore, the Fong study found that a threshold of ≤11 points resulted in a sensitivity of safe discharge at 97% [10]. Similar results were also seen in the 2021 Martin et al study.…”
Section: Discussionsupporting
confidence: 69%
“…As seen in other external validation studies such as the Oakland et al or Fong study, the AUROC for the ability of the Oakland score to safe discharge in LGIB patients was 0.84 compared to 0.87 and 0.88, respectively [9,10]. This is therefore suggesting that the Oakland score is a good tool to predict safe discharge in this cohort of patients as the AUROC > 0.8 [8].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations